Psychological well-being of infertile women and its relationship with demographic factors and fertility history: a cross-sectional study - Farnaz Sohbati; Seyedeh Batool Hasanpoor-Azghady; Mina Jafarabadi; Leila Amiri-Farahani; Marzieh Mohebbi (BMC, 2021)
Abstract Background Infertility leads to a wide range of psychological injuries that may reduce psychological well-being. This study aimed to determine the psychological well-being of infertile women and its relation with demographic factors and fertility history. Methods This cross-sectional study was conducted on 300 infertile women referred to three infertility centres, Tehran, Iran. The sampling was continuous. We collected data from a self-generated demographic and fertility questionnaire and Ryff's Psychological Well-being Scale (PWB). Data analysis was done by independent t-test, one way ANOVA. The significance level was set at P < 0.05. Results The results showed that there was no significant relationship between demographic variables including age, occupation of each couple, spousal's education, economic status and place of residence with PWB, but the mean score of PWB was significantly different in women's educational levels (P = 0.03). There was also a significant difference between the mean score of PWB among different groups in the duration of marriage (P = 0.01). Fertility characteristics variables include the duration of infertility, duration of treatment of infertility, and current treatment were not the relation with PWB. However, the mean score of PWB in the number of IVF (P = 0.003) and the failed IVF pregnancies (P = 0.01) had a significant statistical difference. Conclusion The results showed that PWB related to several variables. Paying attention to these variables can help in the preparation and development of counseling or educational programs.